IN SILICO SCREENING BY MOLECULAR DOCKING OF HETEROCYCLIC COMPOUNDS WITH FURAN OR INDOLE NUCLEUS FROM DATABASE FOR ANTICANCER ACTIVITY AND VALIDATION OF THE METHOD BY REDOCKING - KURIAN, THOMAS (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: This study aims to perform in silico screening of nine heterocyclic ligands containing furan or indole with oxygen in their structure selected from the compound database based on a literature review for predicting their anticancer activity on tyrosine kinase receptor receptors. Methods: The receptor is complex with the ligand Gliteritinib and was downloaded from the protein database. The ligands used for this study were 5-fluoro-1H-indole-2-carboxylic acid,2(5H)-Furanone Furfuryl pentanoate, Furan-2,5-dicarbaldehyde, 2,5-Furandicarboxylic acid, Furan-2-yl(1H-indol-3-yl) methanone, Tert-butyl 3-formyl-1H-indole-1-carboxylate,7-Amino-5-fluoroindolin-2-one,7H-Furo[3,2-g]chromen-7-one. Pyrex molecular docking software was used to perform the analysis. The study was validated using a re-docking technique using the ligand Gliteritinib. Results: A good docking score of (-7.8) was obtained for tert-butyl 3-formyl-1H-indole-1-carboxylate, leading to promising activity prediction. Furan-2-yl(1H-indol-3-yl) methadone and 7H-Furo[3,2-g]chromen-7-one also scored well with (-7.5) and (-7.3) respectively. The redocking process resulted in a score of (-9.2). Conclusion: Values are comparable to the root primary square value, showing the reproducibility of this method. The finding gives insight into Insilco docking for anticancer activity and further exploration of phytochemicals for Insilco screening.